Global Governance: Concept and Fields - Mahmoud, Anwar Mohammed Faraj (Journal of Legal and Political Studies, 2014)
There are discussions and debates between researchers in the field of international relations in the definition of the meaning of the term (Global Governance), there are those who focus in the definition of the actors who make the decisions and policies in the space of global governance, and some of them focus on how to make and implement laws, rules and standards that create a space of global governance, and some of them focuses on joint efforts and cooperative frameworks that attempt to solve global problems that are beyond the capacity of nation-states alone, there are focus in the definition of the (Laws and Rules soft) more than (Laws and Rules solid) and focuses on the (soft power) more of (hard power). Despite the fact that global governance has not reached the level of world government, but covers the broad areas starting from the field of human ethical and moral community to the global economy and the end of the field of world Politics. It contains these areas many topics starts from the topics of human rights and human liberties to the themes and issues of financial and economic activities as well as global issues and political developments as well as the efforts of the institutional and organizational efforts to deal with dilemmas and problems that exceed the capabilities of nation-states and intergovernmental organizations
Keywords: Global Governance; international relations; Laws; Rules; intergovernmental organizations